Efficient Valid Scope Computation for Location-Dependent Spatial Queries in Mobile and Wireless Environments - LEE, Ken C. K. (Institutional Knowledge at Singapore Management University, 2009)
In mobile and wireless environments, mobile clients can access information with respect to their locations by submitting Location-Dependent Spatial Queries (LDSQs) to Location-Based Service (LBS) servers. Owing to scarce wireless channel bandwidth and limited client battery life, frequent LDSQ submission from clients must be avoided. Observing that LDSQs issued from similar client positions would normally return the same results, we explore the idea of valid scope, that represents a spatial area in which a set of LDSQs will retrieve exactly the same query results. With a valid scope derived and an LDSQ result cached at the client side, a client can assert whether the new LDSQs can be answered with the maintained LDSQ result, thus eliminating the LDSQs sent to the server. As such, contention on wireless channel and client energy consumed for data transmission can be considerably reduced. In this paper, we design efficient algorithms to compute the valid scope for common types of LDSQs, including nearest neighbor queries and range queries. Through an extensive set of experiments, our proposed valid scope computation algorithms are shown to significantly outperform existing approaches.